Pengaruh Perencanaan Keuangan, Kemampuan Finansial dan Risiko Investasi terhadap Minat Investasi Emas pada Aplikasi DANA : Studi Kasus Pada Generasi Z Pakisjaya Karawang - Widiah Anggraini; Sihabudin Sihabudin; Robby Fauji (Journal of Management and Creative Business, 2026)
This study aims to determine how financial planning, financial capability, and investment risk influence Generation Z in Pakisjaya District, Karawang Regency, to determine how financial planning, financial capability, and investment risk influence their desire to invest in gold through the DANA app. This study utilized a quantitative approach using descriptive and verification techniques. A sample of 96 respondents was selected through purposive sampling, and a questionnaire was used for data collection. IBM SPSS software was used to conduct multiple linear regression data analysis. The results indicate that financial planning, financial capability, and investment risk partially have a positive and significant effect on gold investment interest. Furthermore, simultaneous testing results indicate that all three independent variables significantly influence gold investment interest, with a coefficient of determination of 83.3%. These results indicate that Generation Z is more interested in gold investment due to the following factors: sound financial planning, sufficient financial capability, and an understanding of investment risk. Furthermore, this research is expected to help develop digital investment studies and serve as a practical reference for Generation Z in making more planned and logical investment decisions.